The Effect of Self-Efficacy, Motivation and Learning Simulation Competence of Polytechnic of Science Shipping Taruna Semarang - Yuliani, Yuliani; Fakhruddin, Fakhruddin; Kardoyo, Kardoyo (Educational Management, 2019)
Competence cadets can affect the level of output, which is generated in the process of education and learning. The factors that affect the competencies include self-efficacy, motivation, learning simulations. To determine how much influence the research is conducted. The aim of researchers to test and analyze the effects of self-efficacy, motivation and learning simulations for the competence of cadets at the Polytechnic of Semarang Sailing Sciences. This study uses a quantitative approach descriptive correlational design using a questionnaire as data collectors. The study population as much as 172 cadets with a sample of 120 cadets. The results showed: (1) self-efficacy negative direct effect on learning simulations with significant values ​​of 0840 (> 0050) and the beta value (-0056). (2) motivation negative direct effect on learning simulations with significant values ​​of 0057 (> 0050) and the beta value (0530). (3) self-efficacy positive direct effect on the competence with significant values ​​of 0000 (<0.050) and the beta value (0719). (4) motivation positive direct effect on the competence with significant values ​​of 0000 (<0.050) and the beta value (0281). (5) simulation learning negative direct effect on the competence with significant values ​​of 0331 (> 0050) and the beta value (-019). From these data indicate that self-efficacy and motivation to improve the competence of cadets. (3) self-efficacy positive direct effect on the competence with significant values ​​of 0000 (<0.050) and the beta value (0719). (4) motivation positive direct effect on the competence with significant values ​​of 0000 (<0.050) and the beta value (0281). (5) simulation learning negative direct effect on the competence with significant values ​​of 0331 (> 0050) and the beta value (-019). From these data indicate that self-efficacy and motivation to improve the competence of cadets. (3) self-efficacy positive direct effect on the competence with significant values ​​of 0000 (<0.050) and the beta value (0719). (4) motivation positive direct effect on the competence with significant values ​​of 0000 (<0.050) and the beta value (0281). (5) simulation learning negative direct effect on the competence with significant values ​​of 0331 (> 0050) and the beta value (-019). From these data indicate that self-efficacy and motivation to improve the competence of cadets. (5) simulation learning negative direct effect on the competence with significant values ​​of 0331 (> 0050) and the beta value (-019). From these data indicate that self-efficacy and motivation to improve the competence of cadets. (5) simulation learning negative direct effect on the competence with significant values ​​of 0331 (> 0050) and the beta value (-019). From these data indicate that self-efficacy and motivation to improve the competence of cadets.